Does the Addition of Naloxone in Buprenorphine/Naloxone Affect Retention in Treatment in Opioid Replacement Therapy?: A Systematic Review and Meta-Analysis. Issue 4 (October 2019) - Dalton, Kathryn; Butt, Natalie
Abstract: Background: Opioid maintenance therapy is an evidence-based first-line treatment approach to reduce the problems associated with opioid use disorders. Buprenorphine and methadone are the two most commonly recommended pharmacotherapies. Individuals who remain in treatment longer tend to have a reduced drug use, a higher social functioning, and a higher quality of life. The addition of naloxone to buprenorphine (bup/nx) was developed, in part, to help increase retention in treatment. However, this has not been shown in research. The objective of this review was to examine whether bup/nx is more effective than buprenorphine and methadone, to ultimately determine whether the addition of naloxone shows a clinical difference. Methods: The literature search was conducted using the electronic databases PubMed, Embase, and Cochrane. Search strategies were thoroughly developed and modified for each database by combining relevant MeSH and Emtree terms as well as keywords such as "bup/nx, " "buprenorphine, " and "naloxone." The outcome measure was treatment retention, as determined by the number of days a participant remains in a treatment program. Results: There were four studies included in the review. The data were analyzed with Review Manager software. There was no statistically significant result for bup/nx compared with methadone or buprenorphine. Conclusion: Bup/nx may be an alternative to standard treatments such as buprenorphine and methadone as the addition of naloxone does not affect retention in treatment.